1314 Availability of video laryngoscopes within 2 tertiary United Kingdom paediatric hospitals. (17th August 2022) - Jackson, Simon; Rafferty, Ben
Abstract : Aims: As part of intra-hospital resuscitation teams, Paediatric Intensive Care (PIC) and Anaesthetic trainees may be expected to intubate children in locations outside their familiar environment of Paediatric Intensive Care Units or Theatres. VL is increasingly used to intubate within PICU, which occurs at the expenses of learning the skill of DL. 1 There are strong arguments for using VL, however an intubator needs to be competent in using all tools (VL or DL) when required. We undertook an audit with the primary aim of assessing availability of VL outside of Paediatric Intensive Care Units and Theatres in 2 tertiary paediatric hospitals. Methods: We reviewed all the resuscitation trolleys on the paediatric wards and Accident and Emergency Departments (AED) in 2 tertiary paediatric United Kingdom hospitals in January 2022. We assessed what laryngoscopes were available (VL and/or DL), whether they were working and if suitable sizes of blades were available. Results: The results can be viewed in table 1 . Hospital 1 had two resuscitation trolleys per ward and had seven wards. Hospital 2 had one resuscitation trolley per ward and had seven wards. Hospital 1 AED had two resuscitation bays with two resuscitation trolleys, but one VL trolley containing two VL. Hospital 2 AED had two resuscitation bays and two resuscitation trolleys. Within AED, Hospital 1 had a MacGrath VL and Hospital 2 had a C-Mac and Ambu VL available. Conclusion: In conclusion, whilst there is increased emphasis for PIC training with VL, it is important to maintain DL competency as paediatric wards only stock DL equipment. If trainees don't invest time to be proficient in both VL and DL, then when intubating with unfamiliar equipment, there is a potential to cause harm to patients. Reference: Grunwell J, Kamat P, Miksa M, Krishna A, et al. Trend and outcomes of video laryngoscope use across picus. Pediatr Crit Care Med . 2017;18:741-749.